A Review on the Contemporary Development of Composite Materials Comprising Graphene/Graphene Derivatives - Fenfen Li; Linyu Long; Yunxuan Weng (Advances in Materials Science and Engineering)
As two-dimensional materials with a high specific surface area, strength, and electrical and thermal conductivity, graphene (Gr) and its derivatives have great application prospects in various fields such as structural reinforcement, energy storage, optics, and electrical and thermal conductivity. However, the current preparation method of Gr is complicated and expensive. Its preparation cost can be reduced using Gr composites that include inorganic materials or other polymers. Composite materials comprising Gr and inorganic materials are generally prepared using sinter molding, chemical reduction, or chemical deposition. Gr should be able to mitigate several of the defects resulting from inorganic materials, including their poor toughness, small specific capacity, and low photoelectric conversion rate. The mitigation of these defects should result in the expansion of the applications of Gr composites for use in capacitors, catalysts, and sensors, among other devices. Although solution blending or in situ polymerization produces a relatively good mixing effect, in general, melt blending is used in the large-scale processing of Gr composites with polymer materials. Gr can be used to partially mitigate several weaknesses of polymer materials, including their low strength, poor electrical and thermal conductivities, and poor isolation performance, and expand the applications of Gr composites for use in electrical and thermal conductive materials and functional membrane materials, among other applications. The goal of the present paper is to introduce the structural properties of Gr and a surface modification method for Gr. In addition, the preparation methods and application fields of different Gr composite materials are reviewed. Finally, the development prospects and key issues are discussed.